Das leere Haus : Spuren jüdischen Lebens in Schwaben ; Fotografien und Essays - Paulus, Martin 1961- Mitwirkender; Paulus, Stefan 1973- Mitwirkender; Raim, Edith 1965- Mitwirkender; Seligmann, Rafael 1947- Mitwirkender (Volk, 2013)
Mit Glossar, Literaturauswahl